Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. A Proposed Training Program for Developing Technology Integration Skills in Basic Education  for Social Studies Teachers in Sana'a City in Light of Their Training NeedsAsst-Prof. Nabil Abdullah Qaid Al-Emad, Co-Prof. Abdussalam Mohammed Ahmed Al-Salahi, Co-Prof. Najat Hasan Hasan Al-Faqeeh2. Achievement Motivation Levels and Their Relationship with Social Cohesion among Basketball Students at the College of Sports SciencesMs. Lama Mamdouh Alkhraishah3. The Effectiveness of Digital Storytelling at Increasing Learning Motivation in Early Childhood  from the Female Teachers' Point of ViewMs. Haya Saud Alshahrani4. The degree of public school teachers' acceptance of using the blended learning approach in the first three basic grades in the Southern Badia Education DirectorateDr. Mahmoud Khalaf Al-Mashaqba5. The level of awareness of elements of national heritage among intermediate school students  in the city of AbhaMr. Ali Essa Hadi Masmali, Prof. Mesfer Ahmad Mesfer Alwadai6. The reality of teaching the digital skills course in the primary school: challenges and solutions  in light of digital transformationDr. Mohamed Saeed Alhabish, Mr. Ahmed Mohsen Alqarni, Mr. Ali Mohammed Alqarni , Mr. Abdulrahman Mohammed Alghamdi, Mr. Asim Homod Albarbi , Mr. Abdulkarim Saleh Almuntashiri7. Special Education in the United States of America and the Potential for Benefit in the Kingdom of Saudi ArabiaMs. Nada Nasser Alqahtani
Keywords: Journal of Curriculum and Teaching Methodology